Toxic epidermal necrolysis in an infant induced by drug intake through breast milk - Yeh-Ni Chu; Ming-Sheng Lee; Shun-Cheng Yang; Hui-Chun Tai; Wen-Hung Chung; Tsu-Man Chiu (Wolters Kluwer Medknow Publications, 2019)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening severe cutaneous adverse drug reactions, and SJS/TEN in infancy is rare. Here, we present a case of a 4-month-old infant with generalized exanthema, flaccid blisters, and mucosal erosions. He was diagnosed with TEN within 2 days using a granulysin quick screen test and subsequently verified with histopathologic findings. Transmission of cephalexin through breastfeeding was suspected to be a possible cause based on drug history, breastfeeding history, and lymphocyte transformation test. The patient survived with only skin hyperpigmentation remaining.